Internalisation of the bedience values to the Baladang-Bakabau tradition in social studies learning - Yuliantoro; Dewi Liesnoor Setyowati; Thriwaty Arsal; Apik Budi Santoso (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
Environmental damage resulting from declining public awareness has prompted the need for solutions based on local traditions. Tradition is a cultural practice that regulates communal living patterns in an orderly manner. The Baladang-Bakabau tradition is an artistic practice that embodies the value of obedience in maintaining the balance of the social and natural environment. This study aims to uncover the perfection of the obedience values within this tradition and formulate a concept for character education to be integrated into social studies learning. The study used a qualitative approach with data collection techniques through interviews with traditional elders, traditional figures, and village heads; observation of the practice of obedience values; and photo documentation of the research objects and literature review. The research results indicate that the obedience values within the Baladang-Bakabau tradition have been internalised through behaviours of togetherness (mutual respect, helping, and sacrificing), cooperation (mutual understanding, sharing roles, and building closeness), and responsibility (cooperation and deliberation). These values provide an answer to the problem of environmental damage and have the potential to be conceptually transformed into social studies learning materials and examples to strengthen students' character education.